Activation of Mitogen-Activated Protein Kinase in Descending Pain Modulatory System. (17th October 2010) - Imbe Imbe, Hiroki Hiroki; Senba Senba, Emiko Emiko; Kimura Kimura, Akihisa Akihisa; Donishi Donishi, Tomohiro Tomohiro; Yokoi Yokoi, Isao Isao; Kaneoke Kaneoke, Yoshiki Yoshiki
Abstract : The descending pain modulatory system is thought to undergo plastic changes following peripheral tissue injury and exerts bidirectional (facilitatory and inhibitory) influence on spinal nociceptive transmission. The mitogen-activated protein kinases (MAPKs) superfamily consists of four main members: the extracellular signal-regulated protein kinase1/2 (ERK1/2), the c-Jun N-terminal kinases (JNKs), the p38 MAPKs, and the ERK5. MAPKs not only regulate cell proliferation and survival but also play important roles in synaptic plasticity and memory formation. Recently, many studies have demonstrated that noxious stimuli activate MAPKs in several brain regions that are components of descending pain modulatory system. They are involved in pain perception and pain-related emotional responses. In addition, psychophysical stress also activates MAPKs in these brain structures. Greater appreciation of the convergence of mechanisms between noxious stimuli- and psychological stress-induced neuroplasticity is likely to lead to the identification of novel targets for a variety of pain syndromes.